Democratic Governance and Industrial Relations in Nigeria - Udeobasi, O. C; Uzoh, B. C. (Social Science Research, 2022)
The aim of industrial relations is to espouse the spirit of peaceful relations between labour and management. Beyond that the existing political climate is fundamental to the development of a less adversarial industrial relations system. While the popular notion is that conflict is inevitable in work organizations, this paper argues that if the methods of conflict resolution are systematically deployed and stakeholders in the industrial relations system of the country adhere strictly to collective agreements, then the incidences of industrial disputes will be reduced to the barest minimum. This paper therefore x-rays the industrial relations climate in the country under the current democratic dispensation against the high incidence of industrial conflicts in the country. The paper contends that unless collective bargaining becomes entrenched in Nigeria’s industrial relations system and the collective agreements emanating from them frequently honoured by all parties concerned, industrial peace will continue to be difficult to come by. The paper thus recommends that parties to collective agreements, especially the government should always endeavor to honour the agreements in order to maintain industrial peace and harmony.